Dispersion of a solute in peristaltic motion of a couple stress fluid through a porous medium - Radhakrishnamacharya, G.; Alemayehu, Habtu (Tamkang Journal of Mathematics, 2012)
The paper presents an analytical solution for dispersion of a solute in the peristaltic motion of a couple stress fluid through a porous medium in the presence of both homogeneous and heterogeneous chemical reactions. The average effective dispersion coefficient has been found using Taylor's limiting condition and long wavelength approximation. The effects of various relevant parameters on the average coefficient of dispersion have been studied. The average effective dispersion coefficient increases with permeability parameter but decreases with homogeneous chemical reaction rate parameter, couple stress parameter and heterogeneous reaction rate parameter.